Jñāna Yoga (Yoga of Wisdom) in Hinduism: With Special Reference to the Bhagavad Gītā - Panda, Prajñā (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 1 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
The Jñāna Yoga literally means “the path of union through knowledge. The Bhagavad Gītā is one of the most influential treatises in Indian philosophy. It is the eternal message of spiritual wisdom from ancient India. It identifies Jñāna yoga as one of the three main paths to liberation, the path of knowledge, the path of action and the path of devotion. There are other paths, but these three are important and effective. While the path of devotion is described as superior to the other two, Jñāna yoga is suitable for people who are deeply intellectual. On the path of liberation it is important to possess right knowledge, which comes through the study of the scripture and helps us understand the significance of other yogas such as karma yoga, sanyāsa yoga, buddhi yoga, ātma samyama yoga, and bhakti yoga. Regarding the importance of Jñāna it is well said in the Bhagavad Gītā (IV.38) It means, there is nothing on earth equal in purity to wisdom. He who becomes perfected by yoga finds this of himself in his self in course of time. Hence, perfect and real knowledge is the best thing in this world. One should try to acquire true knowledge from sacred texts as well as from the great teacher for accruing peace and prosperity in life. However, Jñāna (wisdom or knowledge) is considered the most difficult of the four main paths of Yoga, requiring great strength of will and intellect. In Jñāna yoga, the mind is used to inquire into its own nature and to transcend the mind’s identification with its thoughts and ego. Hence, the Jñāna Yoga is one of the methods for attaining liberation and union with God prescribed by the incarnate Lord Krishna to his friend and disciple Arjuna in the Bhagavad Gītā . This paper will highlight all the features of Jñāna yogas as described in Bhagavad Gītā.